2000
DOI: 10.1007/bf03018925
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of the hemodynamic consequences of theophylline intoxication with landiolol in halothane-anesthetized dogs

Abstract: Purpose: To examine the effect of landiolol (ONO-1101), a new ultra-short acting, highly selective beta 1 blocker, on hemodynamic response to acute theophylline intoxication in anesthetized dogs.Methods: Thirty-four dogs were studied during halothane anesthesia. Aminophylline (50 mg·kg -1 over 20 min followed by infusion at 1.75 mg·kg -1 ·hr -1 ) was administered as a model of acute theophylline intoxication. Dogs were randomly enrolled into four landiolol groups (0, 1, 10, 100 µg·kg -1 ·min -1 ) to treat tach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…D Di is sc cu us ss si io on n The present study demonstrated that chronotropic control was achieved with a landiolol dose of 10 µg·kg -1 ·min -1 . These results are consistent with our previous report 13 that a 10 µg·kg -1 ·min -1 dose of landiolol suppressed tachycardia-induced theophylline intoxication. In another report, 14 Sugiyama et al demonstrated that the isoproterenol-induced increase in HR was halved by 1.5 ± 0.9 µg·kg -1 ·min -1 of landiolol or by 9.3 µg·kg -1 ·min -1 of esmolol in halothaneanesthetized dogs.…”
Section: Me Et Th Ho Od Ds Ssupporting
confidence: 94%
See 1 more Smart Citation
“…D Di is sc cu us ss si io on n The present study demonstrated that chronotropic control was achieved with a landiolol dose of 10 µg·kg -1 ·min -1 . These results are consistent with our previous report 13 that a 10 µg·kg -1 ·min -1 dose of landiolol suppressed tachycardia-induced theophylline intoxication. In another report, 14 Sugiyama et al demonstrated that the isoproterenol-induced increase in HR was halved by 1.5 ± 0.9 µg·kg -1 ·min -1 of landiolol or by 9.3 µg·kg -1 ·min -1 of esmolol in halothaneanesthetized dogs.…”
Section: Me Et Th Ho Od Ds Ssupporting
confidence: 94%
“…Animal preparation was similar to that described previously. 8,13 Animals were anesthetized with 25 mg·kg -1 pentobarbital iv, the trachea intubated with a cuffed tracheal tube, and the lungs ventilated mechanically. Anesthesia was maintained with 1. were randomly assigned according to computer-generated random numbers into one of two groups (n = 9 in each): 1) a milrinone group, or 2) a control (normal saline) group.…”
Section: Me Et Th Ho Od Ds Smentioning
confidence: 99%